The Complete Chloroplast Genome of Arabidopsis thaliana Isolated in Korea (Brassicaceae): An Investigation of Intraspecific Variations of the Chloroplast Genome of Korean A. thaliana - Jongsun Park; Hong Xi; Yongsung Kim (International Journal of Genomics)
Arabidopsis thaliana (L.) Heynh. is a model organism of plant molecular biology. More than 1,700 whole genome sequences have been sequenced, but no Korean isolate genomes have been sequenced thus far despite the fact that many A. thaliana isolated in Japan and China have been sequenced. To understand the genetic background of Korean natural A. thaliana (named as 180404IB4), we presented its complete chloroplast genome, which is 154,464 bp long and has four subregions: 85,164 bp of large single copy (LSC) and 17,781 bp of small single copy (SSC) regions are separated by 26,257 bp of inverted repeat (IRs) regions including 130 genes (85 protein-coding genes, eight rRNAs, and 37 tRNAs). Fifty single nucleotide polymorphisms (SNPs) and 14 insertion and deletions (INDELs) are identified between 180404IB4 and Col0. In addition, 101 SSRs and 42 extendedSSRs were identified on the Korean A. thaliana chloroplast genome, indicating a similar number of SSRs on the rest five chloroplast genomes with a preference of sequence variations toward the SSR region. A nucleotide diversity analysis revealed two highly variable regions on A. thaliana chloroplast genomes. Phylogenetic trees with three more chloroplast genomes of East Asian natural isolates show that Korean and Chinese natural isolates are clustered together, whereas two Japanese isolates are not clustered, suggesting the need for additional investigations of the chloroplast genomes of East Asian isolates.